Strengthening Product Branding and Marketing Optimization Through Social Media on Bamboo Straw Crafts in Abuan Bangli Village - Putri Ekaresty Haes; I Gusti Ngurah Agung Adhi Krisna Murti (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
The distribution of goods and services requires marketing to reach potential customers. The development of internet technology has expanded the marketing of goods and services from traditional to online markets. The bamboo straw craftsmen in Abuan Bangli Village realized that marketing their products online needed to be done to increase the market share of their handicraft products which are currently distributed offline. The National Education University Real Work Lecture Team (KKN) conducted "Strengthening Product Branding and Optimization to Market Bamboo Straw Craft Products in Abuan Bangli Village" for bamboo creative economy actors in Abuan Village who have not or have not used social media optimally as a marketing channel and promotion of bamboo handicraft products. This KKN aims to increase the knowledge of bamboo craftsmen in using social media to support marketing and distribution of bamboo handicraft products directly to customers and sales agents. Social media skills are expected to invite buyers, and increase the income of bamboo craftsmen.